2009
DOI: 10.1055/s-0029-1224874
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean Scar Ectopic Pregnancy: Case Series and Review of the Literature

Abstract: Cesarean scar ectopic pregnancy is becoming increasingly common at tertiary care hospitals around the world. It is a condition in which the embryo implants within the myometrium at the site of a previous cesarean hysterotomy, and it can occur in women with only one prior cesarean delivery. We present four cases of cesarean scar ectopic pregnancy diagnosed within a 6-month period between 2007 and 2008. Their initial presentations and management are discussed, followed by a review of the published literature sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 29 publications
0
80
0
11
Order By: Relevance
“…Though the classification is different, in a larger study, Hwang et al [16] reported better success rates with D&E or D&E under laparoscopic guide. Also compared to 46% of success rate in D&E treatment group, our report showed more increased success rate with 64% [17]. Taken together, for successful evacuation, surgery at earlier gestational weeks is one of the determining prognostic factors.…”
Section: Discussionmentioning
confidence: 46%
“…Though the classification is different, in a larger study, Hwang et al [16] reported better success rates with D&E or D&E under laparoscopic guide. Also compared to 46% of success rate in D&E treatment group, our report showed more increased success rate with 64% [17]. Taken together, for successful evacuation, surgery at earlier gestational weeks is one of the determining prognostic factors.…”
Section: Discussionmentioning
confidence: 46%
“…Erken tanı konulmazsa maternal ölüm görülebilmektedir. Risk faktörleri arasında geçirilmiş sezaryen öyküsü, myomektomi, dilatasyon ve küretaj (D&C), histeroskopi gibi uterusta skara neden olabilecek işlemler yer almaktadır [1]. Genel olarak 5-6. haftalarda tanı almasına rağmen literatürde 15. haftada tanı alan skar gebeliği mevcuttur, gebelik haftası ilerledikçe spontan rüptür riski de artmaktadır [4].…”
Section: Discussionunclassified
“…Geçirilmiş sezaryen olgularında görülme oranı % 0.15' tir [1]. Fizyopatolojik neden olarak embriyonel dokuların uterusun skar olan bölgesinde penetrasyon kabiliyetinin daha yüksek olması gösterilmektedir [2].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Pain and bleeding are the most common presenting symptoms, but up to 40% women are asymptomatic. 1,2 Complications, such as uterine rupture and massive hemorrhage, may be lifethreatening and impact negatively on future fertility. Management options include methotrexate treatment, curettage, hysteroscopic resection, resection by laparotomy/laparoscopy and hysterectomy.…”
Section: Introductionmentioning
confidence: 99%